(untitled) (Journal of Plant Disease Sciences, 2020)
Seed myco-flora associated with black gram varieties were detected by standard blotter test and agar plate method. Six seed borne fungi were found associated with seeds of black gram varieties, externally, which were Aspergillus flavus, Aspergillus niger, Fusarium oxysporum, Macrophomina phaseolina, Alternaria alternata and Botrytis cinera. The internally seed borne fungi were detected by agar plate method and three fungi identified were Fusarium oxysporum, Macrophomina phaseolina and Alternaria alternata. All the isolated pathogens were found pathogenic to black gram resulting into reduction in seed germination and seedling vigour index. Among all the treatments of fungicides, carbendazim @ 0.2 % was found significantly superior in reducing seed borne myco-flora, increasing seed germination and seedling vigour index, followed by Mancozeb @ 0.2 % and captan @ 0.2 %. Amongst bio-agents, Trichoderma harzianum @ 0.6 % recorded lowest seed myco-flora, increased seed germination and seedling vigour index, followed by T. viride @ 0.6 % and T. hamatum @ 0.6 %.